Gender Representation in Indonesian Government-Mandated ELT Textbooks for Primary Schools - Baiq Septia Ayuningsih; Abd. Rahman; Misnariah Idrus (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This qualitative content analysis examines gender representation in Indonesian government-mandated English Language Teaching (ELT) textbooks for primary schools to assess alignment between national gender equality policies and pedagogical materials. Findings reveal significant divergence from international norms. Character distribution showed female predominance (57% vs. 43% male) with female protagonist, reversing typical 60-70% male dominance documented in ELT materials globally. Linguistic analysis demonstrated balanced pronoun usage (48% masculine, 52% feminine) with zero generic masculine, male-first ordering, or gendered adjectives. Activity representation showed minimal stereotyping with counter-stereotypical examples, though limited to domestic and school contexts. Occupational representation proved critically limited, depicting only one professional role (male teacher), creating symbolic void in career diversity exposure. The textbook successfully translates Kurikulum Merdeka gender equality policies into content, achieving neutrality through bias elimination but not transformation through active norm challenge. The results place this material at the top of the global ELT textbook rankings for linguistic visibility and equality, while exposing the ongoing employment gap. Findings demonstrate compatibility between Islamic values and gender equality, contradicting assumptions about cultural barriers in Muslim-majority contexts. The occupational void represents critical intervention point during formative developmental years. Study contributes empirical evidence of policy-to-practice translation success and identifies actionable pathways for Indonesian educational material improvement.